WAKTU PEMBERIAN LUMPUR SAWIT DAN DOSIS NPK PADA PERTUMBUHAN DAN HASIL JAGUNG MANIS (Zea mays saccharata Sturt.) DI ULTISOL - Daniel Malintang Siagian; Bilman Wilman Simanihuruk; Herry Gusmara (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2019)
[TIME OF GRANTING PALM OIL AND NPK DOSAGE IN GROWTH AND RESULTS OF SWEET CORN (Zea mays saccharata Sturt.) IN ULTISOL]. The objectives of this study were to obtain timing of sludge, NPK dosage and best interaction between NPK fertilizer and timing of sludge for growth and yield of sweet corn. The study was conducted from June to September 2017 at Jl. Al-Hikmah Mosque, Kandang Limun Village, Muara Bangkahulu Subdistrict, Bengkulu City with Ultisol soil type and altitude of 15 m above sea level. The study was arranged in Split Plot Design with two treatment factors and three replications. The first factor as the main plot was the time of giving of sludge 0, 2, and 4 weeks before planting, second factor as subplot was the application of each NPK dosage consisting of 3 treatment levels: 150 kg/ha, 225 kg/ha, and 300 kg/ha. The timing of sludge and NPK doses gave no significant effect on the growth and yield of sweet corn. The timing of sludge two weeks before planting gives better results on the number of leaves. NPK was giving no significant effect on all observed variables.